Milwaukee's Gay People's Union: An Analysis of the Gay Liberation Movement and its Linkage to Religion (1969-1978) - Schmieder, Amanda (My University, 2014)
The homosexual experience in the United States is one which many people are interested in given the times, yet still many do not understand the history behind their struggle for equal rights. Unlike the many publicized revolutions such as the Civil Rights Movement and the Feminist Movement, the Gay Liberation Movement is one that often gets glossed over. There is plenty of scholarship regarding the national movement pertaining to New York, Washington D.C., California, and to some extent Chicago, yet there still lacks scholarship. This study will focus the genesis of the Gay People's Union in Milwaukee, Wisconsin in the wake of the Stonewall Riots. In order to understand just why the group formed a thorough analysis of the origins of the movement, starting with the homophile movement in the 1950s up to the birth of Gay Liberation around the time of the Stonewall Riots is warranted. The main finding within the primary scholarship that will be analyzed pertains to the relationship between religion and sexuality and the players in Milwaukee, mainly focusing on the Council on Religion and the Homosexual. The Gay People's Union played a major role in the Milwaukee scene when fostering a non-violent stance toward Gay Liberation and becoming a community player. The story of the fight for equality in Wisconsin, focusing on Milwaukee is just another Midwest story that has yet to be told.
Keywords: Gay People's Union (Milwaukee, Wis.); Gays--Wisconsin--Milwaukee--History; Gay liberation movement--Wisconsin--Milwaukee; Gay liberation movement--Religious aspects